The potential application of fermented tea as a drink for regulating bone mass - Xu, Qiaolu; Yu, Yikang; Chen, Ke (Frontiers in Pharmacology, 2024)
Currently, there is evidence to suggest the benefits of drinking fermented tea for people with osteoporosis, and based on this, many studies have been conducted on the dosage, exact ingredients, mechanisms, and industrial applications of fermented tea for protecting against osteoporosis. A summary and analysis of studies on the regulation of bone mass by oolong tea, black tea, and their active ingredients (including 39 known catechin compounds) was conducted. It was found that the regulation of bone mass by fermented tea is backed by evidence from epidemiology, animal experiments, and cell experiments. The main active components of fermented tea are tea polyphenols, tea pigments, and trace amino acids. The specific mechanisms involved include regulating bone marrow mesenchymal stem cell osteogenesis, inhibiting osteoclast activity, promoting calcium and phosphorus absorption, reducing inflammation levels, regulating gut microbiota, regulating endocrine function, and inhibiting oxidative stress. In terms of its application, extraction, precipitation, biosynthesis and membrane separation method are mainly used to separate the active ingredients of anti osteoporosis from fermented tea. In conclusion, fermented tea has sufficient theoretical and practical support for regulating bone mass and and preventing osteoporosis, and is suitable for development as a health supplement. At the same time, a large amount of epidemiological evidence is needed to prove the specific dosage of tea consumption.